A New Heat Dissipation Model and Convective Two-Phase Nanofluid in Brittle Medium Flow over a Cone. (23rd October 2021) - Hussain, Azad; Haider, Qusain; Rehman, Aysha; Abdussattar, Aishah; Y Malik, M.
Abstract : A time-dependent convectional flow of a two-phase nanofluid over a rotating cone with the impact of heat and mass rates is elaborated in this article. The instability in the flow field is induced by the cone angular velocity that depends on the time. The Navier–Stokes self-similar solution and the energy equations are obtained numerically. Here, the achieved solution is not only for Navier–Stokes equations but also for the equations of the boundary layers. In this work, the concentration, Brownian motion, and thermal buoyancy effects have important significance. We have assumed viscous dissipation with heat-absorbing fluid. Similarity answers for spinning cones with divider temperature boundary conditions give an arrangement of nonlinear differential conditions that have been handled numerically. The MATLAB methodology BVP4C is used to resolve the reduced structure of nonlinear differential equations numerically. Observation for skin friction and Nusselt number is also taken into account. Velocity and temperature impact is depicted graphically, while the outward shear stress values and heat allocation rate are included in tables.